Growth Mindset Mediates the Influence of Social Support on Interest in Continuing Higher Education - Sukron Makmun; Mustari Mustari; Imam Suyitno; Ahmad Jamalong; Najamuddin Najamuddin; Romansyah Sahabuddin (Mimbar Ilmu, 2025)
Developing superior human resources through higher education is one of the keys to a nation's progress, but public interest in continuing higher education remains a challenge in several regions in Indonesia. This study aims to examine the impact of social support on interest in continuing higher education, as well as the mediating role of growth mindset in this relationship. This quantitative study, using a survey approach, was conducted involving 390 active university students as a randomly selected sample. Data were collected through questionnaires and analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS). The results showed that social support has a positive and significant influence on interest in continuing higher education. Social support was also shown to significantly increase growth mindset. The most crucial finding is that growth mindset fully mediates the effect of social support on interest in continuing higher education. This means that although social support is important, its impact on interest in continuing higher education is greatly strengthened when the support is internalized into higher self-confidence in the individual. The results of the model goodness-of-fit evaluation indicate that a proportion of the growth mindset variable can be explained by social support of 61.9%, and interest in continuing higher education is explained by social support and growth mindset by 55.6%. The implications of this research highlight the importance of educational policies and intervention programs that focus not only on providing social support but also strategically strengthen individual growth mindsets to increase higher education participation.